Online Learning During the Pandemic COVID- 19: Teachers’ and Students’ Assessment of Sanako Experience - Ghaouar, Nesrine (LANGUAGE ART, 2022)
With the worldwide spread of COVID-19 in March 2020, universities were closed as part of the quarantine procedure. In Algeria, decision-makers asked teachers to apply e-learning in all possible ways to finish the syllabus. In the department of English at Badji Mokhtar University in Annaba, Algeria, the Sanako platform was proposed as the official e-learning platform during the quarantine. With the intention of investigating EFL teachers’ and students’ assessments of their experience using the Sanako platform as an efficient online learning/teaching platform, two questionnaires were used as research tools, the first for teachers and the second for learners. The results showed that Sanako was useful during the quarantine, though both teachers and students faced certain problems.